The Impact of Digital Leadership on Teachers’ Acceptance and Use of Digital Technologies - I Gusti Ketut Arya Sunu (Universitas Pendidikan Ganesha, 2022)
Teachers’ lack of digital competence causes learning not to be carried out optimally. Thus, the challenge for teachers is getting tougher since, in this digital era, technology mastery plays a significant role in creating quality education. Considering the importance of technology and the role of leadership in education, this study aimed to analyses the impact of digital leadership on teachers' acceptance and use of digital technologies. This research was done involving 27 elementary schools in one city. Six teachers from each school were randomly selected to be the study samples. So, there were 162 teachers involved in the research samples. The research data were collected by distributing questionnaires to measure digital leadership and questionnaires to measure teachers' acceptance and use of digital technology. The collected data were analyzed using simple regression analysis with the help of SPSS 20 for windows. The study showed that the significance of the regression direction was 8,581 with a significance (sig.) of 0.000, which indicates that the regression direction is significant. Therefore, it can be concluded that digital leadership significantly influences teachers’ acceptance and use of digital technology. Since digital leadership is needed to increase education quality, it is suggested that the school principals enhance their digital leadership. Since this research was only limited to two variables, it is necessary to do further research involving more independent variables, considering the various factors that may affect the acceptance and use of technology.